Microwave Dielectric Properties of (1-x) Li2MoO4–xMg2SiO4 Composite Ceramics Fabricated by Cold Sintering Process - Ji, Yuping; Song, Kaixin; Luo, Xinjiang; Liu, Bing; Barzegar Bafrooei, Hadi; Wang, Dawei (Frontiers in Materials, 2019)
Cold sintering process was successfully employed to fabricate (1-x) Li2MoO4 - xMg2SiO4 (LMO-xMSO) microwave dielectric ceramics for 5G enabled technology. Dense LMO-MSO ceramics were obtained with high relative density in the range of 85%-100% under the condition of 200 °C and 500 MPa in an hour. X-ray diffraction (XRD), scanning electron microscope (SEM), energy dispersive X-ray spectroscopy (EDS) and Raman spectroscopy showed that both LMO and MSO phases coexist in all composite ceramics, and there is no detectable secondary phase. Composites in LMO-xMSO (0 < x < 0.3) resonated at microwave frequency (~9 GHz) with low relative permittivity (εr) of 5.05~5.3 and high microwave quality factor (Q × f) of 9450 ~ 24320 GHz, which are attractive for the applications of 5G enabled components.